Analysis of export and import of agricultural industry of the Republic of Kazakhstan - Alzhanova Aigul; Mergenbayeva Aziza; Abdikerimova Gulzhanar; Kulanova Darikul; Seidakhmetov Marat (E3S Web of Conferences, 2024)
This article helps to assess the problem of food security in the Republic of Kazakhstan based on the obtainable resources of the agro-industrial complex and statistical data on export and import of products. The publication considers the problem of ensuring the connection between productivity and export opportunities, as well as the need to take into account the import component to ensure the economic growth of the country. In the article, special attention is paid to the indicators established in the national project for the development of the agro-industrial complex in the Republic of Kazakhstan for 2021-2025 and the preliminary results of its implementation. Since there are no clear ways to ensure food safety, we believe that this issue requires a deeper study. The publication proposes measures to ensure this and evaluates their effectiveness. 1 Introduction